Strengthening the CAR‐T cell therapeutic application using CRISPR/Cas9 technology. Issue 10 (21st July 2021) - Sadeqi Nezhad, Muhammad; Yazdanifar, Mahboubeh; Abdollahpour‐Alitappeh, Meghdad; Sattari, Arash; Seifalian, Alexander; Bagheri, Nader
Abstract: Adoptive cell immunotherapy with chimeric antigen receptor T (CAR‐T) cell has brought a revolutionary means of treatment for aggressive diseases such as hematologic malignancies and solid tumors. Over the last decade, the United States Food and Drug Administration (FDA) approved five types of CAR‐T cell therapies for hematologic malignancies, including Idecabtagene vicleucel (Abecma), Lisocabtagene maraleucel (Breyanzi), Brexucabtagene autoleucel (Tecartus), Tisagenlecleucel (Kymriah), and Axicabtagene ciloleucel (Yescarta). Despite outstanding results gained from different clinical trials, CAR‐T cell therapy is not free from side effects and toxicities, and needs careful investigations and improvements. Gene‐editing technology, clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system, has emerged as a promising tool to address some of the CAR‐T therapy hurdles. Using CRISPR/Cas9 technology, CAR expression as well as other cellular pathways can be modified in various ways to enhance CAR‐T cells antitumor function and persistence in immunosuppressive tumor microenvironment. CRISPR/Cas9 technology can also be used to decrease CAR‐T cell toxicities and side effects. Hereby, we discussed the practical challenges and hurdles related to the accuracy, efficiency, efficacy, safety, and delivery of CRISPR/Cas9 technology to the genetically engineered‐T cells. Combining of these two state‐of‐the‐art technologies, CRISPR/Cas9 and CAR‐T cells, the field of oncology has an extraordinary opportunity to enter a new era of immunotherapy, which offers novel therapeutic options for different types of tumors. Abstract : This study highlighted the pivotal role of CRISPR/Cas9 technology in improvement of CAR‐T cell performance in four main ways. First, CRISPR/Cas9 system generates off‐the‐shelf products for third party patients. Second, CRISPR/Cas9 system makes CAR‐T cells resistant to suppressive molecules. Third, CRISPR/Cas9 system significantly reduces CAR‐T related side effects or toxicities. Fourth, CRISPR/Cas9‐based genetic screening is a promising approach to identify molecular targets responsible for optimizing the overall qualities of CAR‐T cells.